Comment on "The latitudinal gradient in recent speciation and extinction rates of birds and mammals". - Tobias, J; Bates, J; Hackett, S; Seddon, N (2008)
Weir and Schluter (Reports, 16 March 2007, p. 1574) used variation in the age distribution of sister species to estimate that recent rates of speciation decline toward the tropics. However, this conclusion may be undermined by taxonomic biases, sampling artifacts, and the sister-species method, all of which tend to underestimate diversification rates at low latitudes.